Parallels and paradoxes explorations in music and society - Barenboim, Daniel 1942-; Said, Edward W. 1935-2003 (Pantheon Books, 2002)
This fascinating exchange between Daniel Barenboim, Music Director of the Chicago Symphony Orchestra and the Deutsche Staatsoper Berlin, and Edward W. Said, the leading expert on the Middle East, grew out of the acclaimed Carnegie Hall Talks. A unique and impassioned discussion about politics and culture, it touches on many diverse subjects: the importance of a sense of place; the differences between writing prose and music; the conductors Wilhelm Furtwangler and Arturo Toscanini; Beethoven as the greatest sonata composer; the difficulty of playing Wagner; the sound at Bayreuth; the writers Balzac, Dickens, and Adorno; the importance of great teachers; and the power of culture to transcend all national and political differences--something they both witnessed when they brought together young Arab and Israeli musicians to play at Weimar in 1999. Although Barenboim and Said have very different points of view, they act as catalysts for each other. The originality of their ideas makes this a book that is both accessible and compelling for anyone who is interested in the culture of the twenty-first century.
Keywords: Beethoven, Ludwig van <1770-1827> -- Criticism and interpretation; Wagner, Richard <1813-1883> -- Criticism and interpretation; Said, Edward W. -- 1935-2003; Barenboim, Daniel -- 1942-; Filosofische aspecten; Interpretatie; Muziek; Sociale aspecten; Gesellschaft; Musik; Philosophie; Music -- Interpretation (Phrasing, dynamics, etc.); Music -- Philosophy and aesthetics; Music -- Social aspects; Gespräch